WAZUP! COMMUNICATION TOOLS IN ORGANIZATIONAL DECISION-MAKING - Husna Mohamad Taib; Norhayati Rafida Abdul Rahim (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2023)
The WhatsApp application has become the latest trend as a communication tool used in organizations to interact with each other. Most of its use is to convey official or personal information and get immediate feedback. Employees can send information and attach text, images, videos, and audio files. Additionally, users can form specific groups through the WhatsApp application. However, it is unclear to what extent WhatsApp is used as a communication tool that supports decision-making in organizations. This study aims to identify the extent to which WhatsApp is used in the organization and employees' perspectives as an internal organizational communication tool supporting employee decision-making. A quantitative survey method was used to distribute this study through email to executives and non-executives from the selected organization, namely the Malaysian Communications and Multimedia Commission (SKMM), a regulatory body organization under the Ministry of Communications and Digital. Based on the findings of the study, WhatsApp is widely used by SKMM staff to share information, manage daily work routines, and make quick and effective decisions. This WhatsApp is considered an alternative that can be used as a communication tool that supports quick decision-making by the staff in the organization. Most of them agree and gain satisfaction from its use, especially when an immediate decision is needed. The study also shows that all MCMC employees need WhatsApp communication during working hours.